The Influence Of Emotional Value, Functional Value, And Social Value On Customer Retention Among Smartfren Service Users In Lhokseumawe City, Aceh Province - Lilik Lestari (Journal of Contemporary Indonesian Islam, 2026)
This study aims to analyse the influence of emotional, functional, and social values on customer retention (study on Smarfre service users). Data for this study were collected through a survey using a questionnaire as a data collection instrument. The respondents in this study were 96 respondents from Lhokseumawe. This study uses a quantitative approach with multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) software. The results of the study indicate that emotional value has a positive and significant effect on customer retention among Smartfren service users in Lhokseumawe City, functional value has a positive and significant effect on customer retention among Smartfren service users in Lhokseumawe City, and social value has a positive and significant effect on customer retention among Smartfren service users in Lhokseumawe City. Emotional, functional, and social values simultaneously influence customer retention.